Mucins and Wnt/β-catenin signaling in gastrointestinal cancers: an unholy nexus - Pai, Priya (Carcinogenesis, 2016)
The Wnt/β-catenin signaling pathway is indispensable for embryonic development, maintenance of adult tissue homeostasis and repair of epithelial injury. Unsurprisingly, aberrations in this pathway occur frequently in many cancers and often result in increased nuclear β-catenin. While mutations in key pathway members, such as β-catenin and adenomatous polyposis coli, are early and frequent occurrences in most colorectal cancers (CRC), mutations in canonical pathway members are rare in pancreatic ductal adenocarcinoma (PDAC). Instead, in the majority of PDACs, indirect mechanisms such as promoter methylation, increased ligand secretion and decreased pathway inhibitor secretion work in concert to promote aberrant cytosolic/nuclear localization of β-catenin. Concomitant with alterations in β-catenin localization, changes in mucin expression and localization have been documented in multiple malignancies. Indeed, numerous studies over the years suggest an intricate and mutually regulatory relationship between mucins (MUCs) and β-catenin. In the current review, we summarize several studies that describe the relationship between mucins and β-catenin in gastrointestinal malignancies, with particular emphasis upon colorectal and pancreatic cancer.